Antioxidant and cytotoxic effects of crude extract from a diatom, Chaetoceros calcitrans and green alga, Nannachloropsis oculata - Goh, Su Hua (2011)
There is a growing trend in research focusing on marine microorganisms such as sponges, seaweeds and micro-algae as a potential source of bioactive compounds. In Malaysia, microalgae are widely used as live feed in shrimp and fish hatcheries. The nutrient-rich source of marine microalgae gives a promising potential to explore its new biomedical applications. This study was carried out to investigate the antioxidant capacity and cytotoxic effects of different polarities of crude solvent extracts namely hexane, dichloromethane, ethyl acetate and methanol from a diatom, Chaetoceros calcitrans and a green alga, Nannochloropsis oculata. The antioxidant properties were determined by 1, 1-diphenyl-2-picrylhrazyl (DPPH) radical-scavenging, ferric-reducing antioxidant power (FRAP), ferrous-ion chelating and folin assays. Results revealed that crude ethyl acetate (EA) extract of C calcitrans contained the highest total phenolic content (3775.67 ± 0.08 mg gallic acid equivalent/g dried extract) and DPPH radical scavenging power (3722.93 ± 2.98 mg Trolox equivalent/g dried extract). The antioxidant activities of extracts from N. oculata were lower compared to the extract from C. calcitrans, except for EA extract of C. calcitrans showed the highest chelating power compared to others. MTT assay was used to determine the cytotoxic properties of crude solvent extracts from C. calcitrans and N. oculata towards various cancer cell lines. Results showed that EA extract of C. calcitrans significantly inhibited the growth of MDA-MB-231 cells among the cancer cell lines tested, with IC50 60 μg/mL only after 72 hours treatment period. Thus, EA extract of C. calcitrans was used in further assay to determine the mode of cell death with three different concentrations : 30 (½ IC50), 60 (IC50) and 120 (2x IC50) μg/mL for 72 hours treatment. In the cell cycle with flow cytometry analysis, EA extract of C. calcitrans arrested the cell cycle of MDA-MB-231 cells at G2/M phase when treated with 60 μg/mL. However, when cells were treated with low concentration (30 μg/mL) of EA extract, significant growth arrest was occurred at G1 phase. Apoptosis was induced when the concentration was increased to 120 μg/mL. The mode of cell death was mainly apoptosis, which was proven by acridine orange/propidium iodide (AO/PI) dual staining method, Annexin V-FITC and DNA fragmentation (TUNEL) assays. Morphology of the treated cells which was observed through AO/PI staining method showed the presence of blebbing cells, chromatin condensation and DNA fragmentation as well as intake of some PI stain, proving that apoptosis has occurred. Early apoptosis was analysed by Annexin V-FITC apoptosis test and DNA fragmentation test showed that DNA was cleaved into fragments. These results indicated the presence of apoptotic cells increased with increasing concentration of the extract. The changes of expression level of apoptotic, and proliferative-related genes caused by EA extracts of C. calcitrans were profiled using multiplex gene expression profiler (GeXP). Cells treated with EA extract for 6, 12 and 24 hours did not show significant changes in the expression levels of most of the pro-apoptotic genes. The expression of pro-apoptotic genes of the cells treated for 48 hours with low concentration (30 μg/mL) of the extract was highly up-regulated. However, the expression level was down-regulated when treated with high concentration of EA extract (120 μg/mL). At 72 hours of treatment period, most of the pro-apoptotic genes especially caspases related genes such as caspases-3, -4, -9, BAK1 and p21 were found to be up-regulated. Conversely, genes that involved in p53 network especially Bax and ING3 as well as anti-apoptotic (Bcl-2) were found to be downregulated. These findings provided some mechanisms of EA extract of C. calcitrans-induced apoptosis in the human breast cancer cells via the caspases induction pathway. In conclusion, C. calcitrans is more cytotoxic compared to N. oculata (solvent extracts). EA extract of C. calcitrans showed the best antioxidant activities and cytotoxicity compared to others, and induced apoptosis in MDA-MB-231 cells. The induction of apoptosis involved important pro-apoptotic genes : p21, casp-3, -4, -9 and Bak1.